Secondary use and scholarly impact of a portfolio of clinical trials with shared individual participant level data: cross sectional study - Erfan Taherifard; Maryam Mooghali; Hollin R Hakimian; Sahil R Mane; Mengyuan Fu; Stephen Bamford; Jesse A Berlin; Karla Childers; Nihar R Desai; Cary P Gross; Debbie Hewens; Richard Lehman; et al. (BMJ, 2026)
Abstract Objective To assess the number, timing, characteristics, and scholarly impact of secondary publications generated using individual participant level data (IPD) from a portfolio of clinical trials shared with external investigators through a data sharing platform. Design Cross sectional study. Setting Yale University Open Data Access (YODA) Project platform. Participants Johnson & Johnson sponsored clinical trials listed on the YODA Project platform with IPD available for external sharing through 2021 and with a full length, peer reviewed publication (that is, primary publication) reporting primary endpoint results by the original trial investigators. Main outcome measures Number, timing, research objectives, analysis type, and scholarly impact of secondary publications using IPD from these trials identified through Web of Science citation searches of primary publications through June 2025. Scholarly impact metrics included journal impact factor, annual citation count, and annual Altmetric Attention Score. Secondary publications were classified as internal (authored by at least one original trial investigator) or external. Results Among 336 eligible trials, 265 (79%) had at least one associated secondary publication, totalling 1167 publications, of which 209 (17.9%) were external. Among external publications with a reported data access mechanism (n=190; 91%), most obtained access through data sharing platforms (n=161; 85%), primarily the YODA Project (n=157; 83%). Over time, the proportion of external publications increased steadily, exceeding 50% of all secondary publications by year 11 and thereafter. Compared with internal publications, external publications were more frequently pooled analyses (151/209 (72%) v 534/958 (55.7%); P